Understanding anticipatory climate governance in Central America: The links between anticipation and policy - Veeger, Marieke; Muidermann, Karlijn; Tulloch Lapresa, Alexander (2019)
Anticipation practices, such as participatory scenarios, quantitative scenarios and visioning processes, are increasingly used to imagine how countries will be affected by climate change and to proactively plan climate strategies that preempt major social, economic, environmental and health impacts of climate variability. These anticipatory practices are increasingly used to guide transformative planning processes in vulnerable sectors such as agriculture and livestock. However, these anticipatory processes have not been scrutinized as mechanisms of steering of the future in present planning processes. Anticipatory practices might incorporate framings that unwillingly reinforce inequalities and injustices, particularly in the vulnerable regions of the Global South.